Penerapan Goal Programming untuk Optimalisasi Penjadwalan Jam Kerja Satuan Pengamanan - Pradjaningsih, Agustina; Rohmatul Aulia, Indriyani; Riski, Abduh (Politeknik Negeri Batam, 2023)
One common challenge in security system management is the scheduling of security guards' work. Proper work scheduling is essential to prevent physical and psychological fatigue, which can negatively impact their performance. The scheduling process is influenced by factors such as the number of security personnel and the shift arrangements. This study aims to apply the goal programming method to optimize the scheduling of security guards. The research utilizes LINGO 17.0 software for assistance. The research process includes problem identification, data collection, determination of variables and parameters, formulation of goal programming models, solving these models using LINGO 17.0 software, analysis of the results, and the compilation of work schedules for security guards. The study's findings indicate that the established constraints have been met, and the number of working hours and days off for security guards has been optimized, resulting in an efficient schedule.